2018
DOI: 10.3389/fmicb.2018.00390
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Circovirus-Like Virus P1 Inhibits Wnt Signaling Pathway in Vivo and in Vitro

Abstract: Porcine circovirus-like virus P1 is an important pathogen of the current pig industry, the infection mechanism is not entirely clear. Wnt signaling pathway plays an important role in the growth of young animals and infection of some viruses. This study was designed to demonstrate the effects of P1 infection on the Wnt signaling pathway. In vivo experiments, we demonstrated the down-regulatory effects of P1 infection in piglets and mice on the downstream components expression levels of Wnt signaling pathway, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Multiple studies have shown that different virus may employ different mechanisms to manipulate the process of Wnt/β-catenin pathway's participation in viral replication [20,21,31]. In this study, β-catenin up-regulated the expression of IFN-β and ISG, inhibited BPIV3 proliferation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Multiple studies have shown that different virus may employ different mechanisms to manipulate the process of Wnt/β-catenin pathway's participation in viral replication [20,21,31]. In this study, β-catenin up-regulated the expression of IFN-β and ISG, inhibited BPIV3 proliferation.…”
Section: Discussionmentioning
confidence: 59%
“…Many other viral infections have been shown to correlate with the functionality of β-catenin. For example, both Porcine Circovirus-like virus and Human Cytomegalovirus inhibit the classical Wnt signal pathway post-infection [8,31]. When Wnt/β-catenin pathway is at the deactivation stage, the protein kinase GSK3β phosphorylates serine at site 33 and 37 on β-catenin [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses can activate or deactivate the Wnt/β-catenin pathway. These include viruses such as HIV [ 31 ], porcine circovirus-like virus P1 [ 21 ], HCMV [ 32 ], and HCV [ 17 ]. On the other hand, the Wnt/β-catenin signaling pathway has varying effects on different viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated the interaction of the Wnt/β-catenin signaling pathway with human and animal viruses, including human immunodeficiency virus (HIV) [ 14 ], herpes simplex virus 1 (HSV1) [ 15 ], hepatitis B virus (HBV) [ 16 ], hepatitis C virus (HCV) [ 17 ], influenza virus (IAV) [ 18 ], porcine reproductive and respiratory syndrome virus (PRRSV) [ 19 , 20 ], porcine circovirus-like virus P1 [ 21 ], bovine parainfluenza virus type 3 [ 22 ], and bovine herpesvirus 1 [ 23 ]. Some of these viruses activate the Wnt/β-catenin signaling pathway, while others deactivate it through diverse mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the cellular events caused by infection with P1 virus. The study showed that several porcine genes, such as MMP2, were down-regulated not only in tissues of infected pigs and mice but also in ST cells and that the virus induces the Wnt signaling pathways [ 20 ].…”
Section: Discussionmentioning
confidence: 99%